Development of a safer laboratory vervet monkey model for the study of human African trypanosomiasis - Maxwell Waema; Naomi Maina; Simon Karanja; Beatrice Gachie; Maina Ngotho; John Kagira (African Journal of Laboratory Medicine, 2014)
Background: There are three subspecies of Trypanosoma brucei: T. b. gambiense, T. b. rhodesiense and T. b. brucei. The first two are infectious to humans, whilst T. b. brucei is not. Identifying an animal model of T. b. brucei that mimics human African trypanosomiasis (HAT) would enable researchers to study HAT without subjecting themselves to undue risks such as accidental infection.